Foreign exchange risk management case study: RJR NABISCO - Primanita Primanita (Universitas Islam Indonesia, 1995)
This article presents a case analysis of RJR Nabisco Holdings Corporation's foreign exchange management. The strategy pursued by RJR Nabisco, the two headed-hedging strategy succeded in lowering it's foreign exchange risk.